Advanced Java development : from generics and collections to concurrency and data access (O'Reilly, 2016)
"You're a junior developer with a couple of years of Java under your belt and you've hit the Java wall of mystery. The knowledge blocker where complex concepts like concurrency and network programming or generics and collections leave you baffled and unable to proceed. In this video, Java wizard Ken Kousen de-mystifies all to transport you to a smarter place. A place where your newfound Java skills work magic into the day-to-day practices of database programming, network programming and back-end web development. Spells uncovered include: generic programming, concurrency, interfaces, inheritance, objects, the new I/O packages, working with relational databases, networking, testing, inner classes, and the new features of Java 8. Put on your cape and zoom."--Resource description page.